Quand l’édifice vacille : stupeur et tremblements dans la gestion du risque après le séisme du Teil - Mathias Roger; Stéphane Cartier (VertigO)
The Teil earthquake of November 11, 2019 defied all predictions. In this article, we follow seismic risk experts in France in their efforts (1) to make sense of a bewildering event and (2) to draw lessons for the protection of conventional constructions and high-risk facilities (chemical and nuclear). This study highlights the strategic position occupied by a community of experts situated between built environments (both residential and industrial) and seismic threats. Through self-referential loops, these experts extinguish controversies and confine the calculation of acceptable risk within a technical bureaucracy that seize the dual task of improving seismic knowledge and mitigating risks.